The future of truth - Herzog, Werner, 1942- (Penguin Press, 2025)
"From legendary filmmaker and author Werner Herzog, a compact, effervescent, and deeply personal exploration of art, philosophy, and history that unravels one of our most elusive and contested questions: what is truth-and how to find it in our "post-truth" era? For over half a century, Werner Herzog has challenged, enriched, and expanded our understanding of the truth. His films and books have mixed fiction and nonfiction, documentary and drama, reality and imagination. Invariably, Herzog goes beyond the appearance of what is true in search of a higher truth, or what he has often referred to as the "ecstatic truth". But never before has he engaged so directly with the question of truth. In The Future of Truth, a great artist essays an answer to one of humanity's deepest, most eternal questions. At a moment when deepfake AI videos are proliferating, and most people have simply thrown up their hands in despair at the ubiquity of what we now know as fake news-not to mention the constant lying and propagandizing from certain public figures-Herzog seeks a remedy. Mixing memoir, history, politics, poetry, science, and fierce opinion, he writes with dazzling originality and panache, urging readers themselves to be unflagging and imaginative in the pursuit of truth, endless though the quest may be: I don't think truth is some kind of Pole star in the sky that we will one day get to. It's more like an incessant striving. A movement towards it, an uncertain journey, a seeking full of futile endeavor. But it is this journey into the unknown, into a vast twilit forest, that gives our lives meaning and purpose; it's what distinguishes us from the beasts in the fields." --